Cross-Sectional Study of Risk Factors for Children's Language and Speech Delays - Ariyanti, Lilik; Semartini, Atur (GLOBAL HEALTH SCIENCE GROUP, 2024)
Teaching children to talk in both directions and to comprehend speech appropriate for their age is an important part of their language development process. There is a direct correlation between a child's language development and brain growth. Parents and the surrounding environment have an impact on a child's growth. The purpose of this study is to identify the risk factors for children's language and speech delays. This cross-sectional study was conducted at Kindergarten in the Grogol District between November 2022 and January 2023. Purposive sampling was used to get samples. A questionnaire was used to obtain the data. The DENVER sheet was used to measure the development. The results showed that the father was employed (40.8%), the mother had a high school degree (55.1%), and the family's income was below the minimum wage (51%). Having standard deviation of 5.65 years, the average age of the first respondents who used gadgets was 3.27. Most of children used gadget for 30 to 60 minutes each day. The average children (59%), who is younger than 4 years old, utilized a device for the first time for 30 to 60 minutes each day. Children performed this 1-2 times a day (65%). 20% of children were included into the questionable group in terms of language development. According to statistical study, maternal education (p value = 0.021) and family income (p value = 0.005) were related. Family income and maternal education are related to children's language and speech delays.